SOCIO-ECONOMIC EFFECTIVENESS OF HEALTH SCREENING ACTIVITY IN 2013 IN RUSSIAN FEDERATION - A. V. Kontsevaya; A. M. Kalinina; S. A. Boytsov; P. V. Ipatov (Кардиоваскулярная терапия и профилактика)
Aim. To estimate long-term socio-economic effectiveness of broad health screening activity of adults by the results in the year 2013.Material and methods. The study is performed with the method of mathematic modelling using the results of completed in the year 2013 health screening and with an estimate for adult productive and economically active age (up to 72) for 10-year perspective of potentially prevented deaths from the main chronic non-infectious diseases (CHID), saved years of life and economic expenses by 1 year of saved life.Results. Through analyzed malignant tumours (MT) maximum deaths are to be prevented from breast cancer. The most significant effect of the performed screening is decrease of cardiovascular (CV) deaths — quantity of potentially saved lifes at productive age during 10 years would be 10 times higher than from MT. Screening for the studied CHID is characteristic for certain economic expediency, because expenses on 1 year of potentially saved life appeared lower than gross domestic product by one inhabitant. The most economic expediency of screening was found at the matter of CV diseases: expenses on 1 year of saved productve life (15,5th RUR) and economically active age (11th RUR), that is significantly lower than domestic gross product by inhabitant. Return of investments into health improvement thank to earlier diagnostics of CHID and further treatment would reach 10 RUR per each invested 1 RUR by 10 years.Conclusion. The analysis and calculations showed a significant positive effect of health screening in 2013, most of all due to earlier diagnostics and complex action against CV diseases and MT, which are included into screening and observation. Expenses on 1 year of saved life were lower than domestic gross product by inhabitant (in prices of the 2013) and return of investment by maintaining labour potential of economically active population was 10 RUR by 1 invested RUR during 10 years. Economic efficiency of health screening as a strategy to prevent premature death, preventable death and to keep health is clear.